O trabalho do serviço social no INSS e a saúde do trabalhador - Oliveira, Tamara dos Santos [UNESP]; Lourenço, Edvânia Ângela de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study discusses the illness dasos social workers who work in Social Security from the extension project "Social Service worker in SOCIAL SECURITY and the worker's health." with special focus to the social relations of labor and Health Social Welfare Service, specifically in the Uberaba/MG agencies, Judge of Fora/MG and Araraquara/SP.

Este estudo apresenta algumas ações do projeto de extensão universitária “O Trabalho do Serviço Social no INSS e a Saúde do Trabalhador”, com enfoque especial para as Oficinas realizadas com as assistentes sociais das agencias da Previdência Social de Uberaba/MG, Juiz de Fora/MG e Araraquara/SP.
Keywords: Social services; Health; Social security; Serviço social; Saúde; Previdência social